Battleground Alaska : fighting federal power in America's last wilderness - Haycox, Stephen W. (University Press of Kansas, 2016)
"Alaska, "the most anti-statist of the American states," has for decades provided high-profile flashpoints for battles between environmentalists and promoters of economic development. Haycox argues that Alaskans' strong anti-statist sentiments (deep distrust of and anger towards federal regulation and control) have greatly amplified and exacerbated the tensions and critical volleys fired between these long-feuding camps. A case study in federal-state relations and environmental-development conflict, his book underscores Alaska's unique and volatile place in American politics and imagination"--